An Evaluation on Investment of Research Funds with a Neural Network Algorithm in "Double First-Class" Universities. (4th November 2020) - Sun, Jihong; Li, Yahui; Zhao, Xiaoyun; Zhang, Nanxing
Abstract : In the current context of the establishment of world-class universities and disciplines in China, this study examined the investment of research funds at universities. First, six variables were selected as evaluation indicators from the perspective of fixed assets, teaching configuration, research instruments, and the number of books in libraries. Seventy-two universities were investigated from 2013 to 2017. Second, an evaluation system was constructed using the BP (backpropagation) neural network method and its applicability was verified. Finally, by adjusting the six indicators, the investment of university research funds could be adjusted and predicted to provide a reference for the construction of "first-class" universities and disciplines.